The cultivation of prana in classical sāṃkhya: Towards a philosophy of shared breathing - Funes Maderey, Ana Laura (2025)
This essay provides a philosophical reading of the notion of prāṇa by showing its ethical dimension in Sāṃkhya philosophy, especially as it appears in the commentary called Yuktidīpikā (8th C.E.). It concludes with a reflection on the implications this notion has for a post-pandemic ethics.